Effect of nutritional supplementation with milk whey proteins in amyotrophic lateral sclerosis patients Efeito da suplementação nutricional com proteínas do soro de leite em pacientes com esclerose lateral amiotrófica - Luciano Bruno de Carvalho Silva; Lucia Figueiredo Mourão; Ariovaldo Armando Silva; Núbia Maria Freire Vieira Lima; Sara Regina Almeida; Marcondes C. Franca Jr; Anamarli Nucci; Jaime Amaya-Farfán (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: We evaluated the efficacy of oral supplementation with milk whey proteins and modified starch (70%WPI:30%MS), on nutritional and functional parameters of patients with ALS. METHOD: A prospective randomized double-blind study was performed with 16 ALS patients, divided in two groups, the treatment group received (70%WPI:30%MS) and the control group received (maltodextrin). They underwent prospective nutritional and functional assessment for 4 months. RESULTS: Patients in the treatment group presented weight gain, increased body mass index (BMI), increased arm muscle area and circumference, higher albumin, white blood cell and total lymphocyte counts, and reduced creatine-kinase, aspartate aminotransferase and alanine aminotransferase. In the control group, biochemical parameters did not change, but weight and BMI declined. CONCLUSION: Our results indicate that the agglomerate 70%WPI:30%MS may be useful in the nutritional therapy of patients with ALS. OBJETIVO: Avaliar a eficácia da suplementação nutricional oral com proteínas do soro do leite e amido modificado (70%WPI:30%MS), nos parâmetros nutricionais e funcionais de pacientes com esclerose lateral amiotrófica (ELA). MÉTODO: Foi realizado estudo randomizado duplo-cego, com 16 pacientes com ELA, divididos em dois grupos, um que recebeu 70%WPI:30%MS e um controle que recebeu maltodextrina. Os pacientes foram submetidos a avaliação nutricional e funcional durante quatro meses. RESULTADOS: Nos pacientes que receberam o suplemento 70%WPI:30%MS, foi observado ganho de peso, aumento na contagem de linfócitos e redução de creatina kinase, aspartato aminotransferase and alanina aminotransferase. No grupo controle, os parâmetros bioquímicos não sofreram modificações; no entanto, peso e índice de massa corporal diminuíram. CONCLUSÃO: Nossos resultados indicam que o aglomerado 70%WPI:30%MS pode ser útil na terapia de pacientes com ALS.